Knowledge transfer through international assignments in the organizational context - Purgał-Popiela, Joanna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The main goal of this paper is to contribute to a better understanding of knowledge transfer within international assignments (IAs). The author‟s intention was to develop a theoretical model which illustrates the complexities of this process, and emphasizes the role of support provided by a company. As the latter is not only an interesting field for theoretical exploration, but also represents an important challenge for managers and assignees in multinational companies, the study provides the conceptual framework, and an exemplification of the above issue based on three Polish MNCs‟ experiences
Argumenta Oeconomica, 2015, Nr 2 (35), s. 145-167
Keywords: international assignments; knowledge transfer; conceptualization; organizational context